#### Answer

$243i$

#### Work Step by Step

$(-3i)^5 = (-3)^5 \cdot i^5 = -243 \cdot i^4 \cdot i = -243 \cdot 1 \cdot i = 243i$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$243i$

$(-3i)^5 = (-3)^5 \cdot i^5 = -243 \cdot i^4 \cdot i = -243 \cdot 1 \cdot i = 243i$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.